PRONERA in a paradigmatic perspective: The experience of Youth and Adult Education in the countryside - Fabíola Andrade Pereira; Severino Bezerra da Silva (Universidade Federal do Norte do Tocantins, 2019)
This article consists a re-reading of a study conducted in mid-2006. The goal was to establish relationship between advisory student and advisor professor. We conducted our reflections on Rural Education and Youth and Adult Education circumscribed in the PRONERA - National Program of Education in Agrarian Reform, which for more than 20 years has been developed in several states of Brazil. The Program is based on the Freirean pedagogical political presuppositions and on the accumulation of educational experiences of organized social movements. In this sense, the approach of our research also sought to reflect on the interface with the evaluation of a public policy, inasmuch as it sought to verify its effectiveness as a reference for rural education at the national level and for the strengthening of Brazilian public education.